Relasi Media Massa Jelang Pemilu 2024 Antara Pemerintah Dan Masyarakat - Baharuddin Baharuddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The relationship between the mass media and the political sphere is a matter of dilemma. Where, the reporting of a media is not completely neutral from political intervention or patronage of power. The media in terms of democracy is a trias politica institution which is the fourth pillar in democracy. The central function of the media is as a media supervisor. The public is guided in consuming both printed and electronic information as well as translating various frenzied realities of national and state life. The media here has power over public knowledge through the framing of text and images so that they become the main reference for the public in forming their opinions on the course of government. Information is the key word that links media relations with politics through the formation of public opinion on the news. This study aims to explain and analyze the tendency of mass media coverage in the context of the 2024 Presidential Election. The research method used is the framing analysis model of Robert N. Entman. The results of the research show that the relations of the mass media in politics by looking at the alignments of the mass media can at least be detected through; Mass media in determining news sources; The media takes advantage of the limitations of columns and pages, the mass media will pay attention to things that are considered urgent from a person or pair of candidates in the election; There is an arrangement of space and place that is wide enough for the activities of a person or pair of candidates, such as reporting on the first page of a newspaper.